The third millennium studies in early Mesopotamia and Syria in honor of Walter Sommerfeld and Manfred Krebernik - Sommerfeld, Walter 1951-; Krebernik, Manfred 1953-; Arkhipov, Ilya; Kogan, Leonid 1973-; Kozlova, Natalija Vadimovna 1948- (Leiden Boston Brill, 2020)
"The Festschrift containing 36 contributions celebrates the scholarly achievements of the two outstanding Assyriologists, Walter Sommerfeld (University of Marburg) and Manfred Krebernik (University of Jena). The primary focus of the volume corresponds to the main topics of interests of Professors Sommerfeld and Krebernik - Pre-Sargonic and Sargonic Mesopotamia and third millennium Syria. The volume also features a few contributions dealing with Sumerian language, Mesopotamian literature and the early history of Akkadian and its Semitic background"--
Includes bibliographical references and index
Essays in English, French, or German
Keywords: Cuneiform tablets -- Iraq; Cuneiform tablets -- Syria; Sumerian language -- Texts; Akkadian language -- Texts; Iraq -- Antiquities; Syria -- Antiquities; Iraq -- Civilization -- To 634; Syria -- Civilization; Aufsatzsammlung; Festschrift